TRADITIONAL GAMES REVISITED: : A NEW PERSPECTIVE ON GROSS MOTOR DEVELOPMENT IN 5-6 YEAR OLD - Salindri, Wiwit (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2024)
This research aims to determine the effect of modifications to traditional games on the gross motor development of children aged 5-6 years. This research is a type of quantitative research using pre-experimental methods with a one-group pretest-post-test design. The sample in this study consisted of 16 children aged 5-6 years. The sampling technique uses purposive sampling. The data collection techniques used in this research are observation and documentation. Observations were carried out using an observation sheet tested for validity, and all indicators were stated as valid. Then, the reliability using Cronbach's alpha formula was declared reliable with a reliability value for variable X of 0.777, and the reliability of variable Y is 0.885. The research results show that the average N-Gain score is 0.43, meaning that traditional game modifications influence children's gross motor development in the medium category. Then, the test results using a simple linear regression test obtained a significance value of 0.001 less than 0.05 (0.001<0.05); this proves that there is an influence between traditional game modifications on the gross motor development of children aged 5-6 years.